Pengaruh Elektroakupunktur Titik Zusanli (ST 36) dan Zhongwan (CV 12) terhadap Perbaikan Gambaran Histologis Duodenum Tikus Putih (Rattus norvegicus) yang Terpapar Bising Intermitten - Fajarini, Nur Dwi; Balgis, .; Handayani, Selfi (Nexus Biomedika, 2014)
Background: Intermittent noise can induce stress that stimulates HPA axis to cause damage of duodenum. Acupuncture has already indicated to treat duodenal ulcer. This research studied the effect of electroacupuncture of Zusanli (ST 36) and Zhongwan (CV 12) acupoints to repair histological structure of white rat (Rattus norvegicus) duodenum exposed by intermittent noise. Methods: This was laboratory experimental research with the post test only controlled group design. Subjects were 28 male white rats (Rattus norvegicus), wistar strain, divided into 4 groups randomly. They were control group (K) which was not treated, experimental group 1 (P1) exposed by noise, experimental group 2 (P2) exposed by noise and allowed to have physiologic recovery for 30 days, and experimental group 3 (P3) exposed by noise and treated with electroacupuncture for 30 days. Noise exposure was conducted for 2 weeks with intensity of 95 dB intermittently, 1 hour on, 1 hour off, for 12 hours daily. Electroacupuncture was done by pricking acupuncture needle perpendicularly at Zusanli (ST 36) and Zhongwan (CV 12) acupoints, then, connected to 2 mA electrostimulation at 10 Hz continuous wave for 15 minutes, 10 times for therapy. At the end of experiment their duodenums were taken and prepared for histologicalÂ study by paraffin block method and stained with Hematoxillin Eosin (HE). The histological structure of duodenal mucosa was observed and assessed for the damage with Barthel Manja mucosal integrity score. The data were analized by One-Way ANOVA test (Î±=0.05) and continued by Post Hoc Multiple Comparisons using Least Significant Differences (LSD) test (Î±=0.05). Results: One Way Anova test showed significant differences of duodenal mucosa damage among the four groups p=0.000. LSD test showed significant differences between K-P1 (p=0.000), K-P2 (p=0.000), K-P3 (p=0.000), P1-P2 (p=0.007), P2-P3 (p=0.000), but not between P1-P3 (p=0.235). Conclusions: Electroacupuncture of Zusanli (ST 36) and Zhongwan (CV 12) acupoints repaired histological structure of white rat (Rattus norvegicus) duodenum exposed by intermittent noise. Keywords: Intermittent noise, Electroacupuncture,Â Zusanli and Zhongwan acupoints, DuodenumÂ